Malaysian secondary school history curriculum and its contribution towards racial integration - Ahmad, Abdul Razaq; Rahim, Ahamad; Seman, Ahmad Ali; Salleh, Mohamad Johdi (Elsevier, 2010)
This paper attempts to review the historical aspects of the problems arises in history education and provides suggestions for someappropriate measures that will enable students to instil values associated with racial relationship. Next, this paper highlightssteps needed to be carried out in schools and the Ministry of Education (MOE) which is hoped to strengthen the teaching andlearning methods in the subject of History. We argue that History education can help to shape the attitudes of tolerances,patriotism, citizenship and values in order to create a united nation through the One Malaysian concept.